Improving Vocabulary Mastery Through the Traditional Game “Engklek” For Children in Kalijaten Village, Kec. Taman, Kab. Sidoarjo - Authar, Nailul; Muflihah, Tatik; Fidyaningrum, Seftia Ani; Hardiana, Alma Shafira; Azizah, Alfiyatul; Ramadhani, Delia (Universitas Nahdlatul Ulama Surabaya, 2021)
Vocabulary is a basic thing that children should know before they learn English because vocabulary will make it easier to understand or master English. In Kalijaten, children tend not to be able to master English and they also have difficulty learning vocabulary. So to help with this the researcer have implemented a method using “engklek” to help improve children's vocabulary in Kalijaten Village. Using these traditional learning media can make it easier for children to improve their vocabulary skills and they will not get bored easily so the possibility of improving the vocabulary can increase. The purpose of holding vocabulary learning through the game “engklek” is to make it easier for children in Kalijaten village to master vocabulary easily. The method used for research is qualitative by collecting data by means of observation to children in Kalijaten village and it also takes 10 days, where the first and second days of surveying the place and collecting data on children in Kalijaten village and the following day the game was held. The place used to research this PKM is in the village of Kalijaten, Taman Subdistrict, Sidoarjo Regency. The length of observation used was two days when the author did practice in the field. The materials used are white chalk, gaco, laminating paper and the vocabulary that has been given. The results have shown that 70% of the children in Kalijaten village have low proficiency in mastering English, especially in vocabulary and 20% of Kalijaten children have a standard ability in mastering English, especially in vocabulary, and 10% of children in Kalijaten village have high skills in mastering vocabulary.